Will CREATE Resolve the Philippines’ Unemployment Woes Amidst the COVID-19 Pandemic? - Yu, Krista Danielle (Animo Repository, 2020)
In response to the COVID-19 pandemic, there is a proposal to amend the Corporate Income Tax and Incentives Reform Act (CITIRA) into the Corporate Recovery and Tax Incentives for Enterprises Act (CREATE) Act. The proposed amendments are as follows: (a) An immediate five percentage point cut into the corporate income tax (CIT) rate starting July 2020; (b) Maintaining for up to nine years the status quo for registered business activities enjoying the 5% tax on gross income earned (GIE) incentive; and (c) More flexibility for the President to grant a combination of fiscal and non-fiscal incentives, which will be critical as the country competes internationally for high-value investments (Department of Finance (DOF), 2020).